Modern Scattering‐Type Scanning Near‐Field Optical Microscopy for Advanced Material Research. Issue 24 (1st April 2019) - Chen, Xinzhong; Hu, Debo; Mescall, Ryan; You, Guanjun; Basov, D. N.; Dai, Qing; Liu, Mengkun
Abstract: Infrared and optical spectroscopy represents one of the most informative methods in advanced materials research. As an important branch of modern optical techniques that has blossomed in the past decade, scattering‐type scanning near‐field optical microscopy (s‐SNOM) promises deterministic characterization of optical properties over a broad spectral range at the nanoscale. It allows ultrabroadband optical (0.5–3000 µm) nanoimaging, and nanospectroscopy with fine spatial (<10 nm), spectral (<1 cm −1 ), and temporal (<10 fs) resolution. The history of s‐SNOM is briefly introduced and recent advances which broaden the horizons of this technique in novel material research are summarized. In particular, this includes the pioneering efforts to study the nanoscale electrodynamic properties of plasmonic metamaterials, strongly correlated quantum materials, and polaritonic systems at room or cryogenic temperatures. Technical details, theoretical modeling, and new experimental methods are also discussed extensively, aiming to identify clear technology trends and unsolved challenges in this exciting field of research. Abstract : Scattering‐type scanning near‐field optical microscopy (s‐SNOM) allows ultrabroadband optical (0.5–3000 µm) nanoimaging and nanospectroscopy with fine spatial (<10 nm), spectral (<1 cm −1 ), and temporal (<10 fs) resolution. Recent progress in the s‐SNOM technique and its application in material research at room and cryogenic temperatures is summarized.